The Effects of Mindfulness-Focused Internet-Based Cognitive Behavioral Therapy on Elevated Levels of Stress and Symptoms of Exhaustion Disorder: A Randomized Controlled Trial - Kristofer Vernmark; Timo Hursti; Victoria Blom; Robert Persson Asplund; Elise Nathanson; Linda Engelro; Ella Radvogin; Gerhard Andersson (Clinical Psychology in Europe)
[Background] Internet-based Cognitive Behavior Therapy (ICBT) and mindfulness interventions are commonly used to treat elevated levels of stress. There are however few high-quality studies that examine ICBT with integrated mindfulness components for symptoms of stress and exhaustion, and the role of mindfulness exercises in digital treatment. [Method] The aim of the present study was to evaluate if a mindfulness-focused ICBT-program could reduce symptoms of stress and exhaustion, and increase quality of life, in a randomized controlled trial including 97 self-referred participants between 18 and 65 years who experienced elevated levels of stress. [Results] The intervention group had significantly reduced symptoms of stress and exhaustion, and increased quality of life, compared to the control group. Compared with the controls, participants in the intervention group showed a significant improvement with moderate to large effects on the primary outcome measure perceived stress (d = 0.79), and the secondary outcomes, exhaustion (d = 0.65), and quality of life (d = 0.40). Participants in the ICBT group also increased their level of mindfulness (d = 0.66) during the program. The amount of mindfulness training was significantly associated with an increased level of mindfulness, which in turn was significantly associated with reduced stress symptoms. [Conclusions] Mindfulness-focused ICBT can be an effective method to reduce stress-related mental health problems and the amount of mindfulness training seems to be of importance to increase the level of experienced mindfulness after treatment.